The twelve days of Christmas - Jay, Alison (Alfred A. Knopf, 2015)
As a couple strolls through town on Christmas Eve, the man buys gift after gift for the woman he loves, and after arriving at a Christmas party so magnificent it is overwhelming, they slip back to their own quiet home.